TINJAUAN EMPIRIS PERAN ISTRI SEBAGAI WANITA KARIR DALAM MENCIPTAKAN KELUARGA SAKINAH - Handayani, Venny Cintya; Latif, Udin (Muadalah : Jurnal Hukum, 2025)
A career woman is an individual who actively participates in the workforce, fulfilling professional roles while managing family responsibilities. The career woman phenomenon has evolved in line with social and economic changes that have opened up more job opportunities for women. Women's primary motivations for pursuing a career include achieving financial independence, self-development, and fulfilling professional ambitions. Support from partners, family, and flexible workplace policies can play a significant role in helping career women achieve a balance between their professional and personal lives.This research employed a qualitative approach. The sample population was career women in Malawili Village. Data collection methods used observation, interviews, documentation, and data analysis, including data reduction, data display, and conclusion drawing. The results of this study indicate that a wife's responsibilities as a career woman often face unique challenges, including time management, the pressure to balance dual roles as worker and caregiver, and confronting gender norms and stereotypes. The Sakinah family is a family concept in Islam that describes a harmonious, peaceful, and prosperous household.